SURFACE ACIDITY CONSTANTS OF α-AL2O3 BETWEEN 25 AND 70°C - AN INTRODUCTION - Halter W.E. (My University, 1999)
The effect of temperature on the adsorption of H+ onto corundum was investigated experimentally by conducting potentiometric titrations at 25, 30, 40, 50, 60 and 70°C. These titrations were used to determine apparent acidity constants, given by the product of an intrinsic adsorption constant and a coulombic term (Kiapp = Kiinte(-ΔZFΨ/RT)) at the above temperatures.First and second intrinsic acidity constants were determined using a constant capacitance model (CCM). These constants and the point of zero charge change linearly with inverse temperature. These data were used to determine thermodynamic constants for the proton adsorption reactions.In the coulombic term, only the capacitance and the surface charge change with temperature and both were determined with the titration data at the various temperatures. Results show that the change in capacitance can be predicted with changes in the dielectric constant of water with increasing temperature. At a given pH, changes in the surface charge with temperature can, in turn, be predicted with a linear regression.With the above model, apparent acidity constants of corundum (including the chemical and electrostatic interactions) can be predicted for any temperatures between 25 and 70°C and possibly higher. These apparent constants change over several orders of magnitude in this temperature range (mainly due to a change in the coulombic term) and small temperature changes could have a strong influence on the stability of surface complexes.